2017
DOI: 10.3892/etm.2017.5591
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin causes apoptosis by disrupting intracellular calcium homeostasis and mitochondrial function in human hepatoma cells

Abstract: Shikonin is known to suppress proliferation and induce apoptosis in a variety of cancer cell lines. In the present study, SMMC-7721 human hepatocellular carcinoma cells were treated with shikonin (1, 2 or 4 µM) for 12–48 h. Cell morphological alterations and DNA damage were determined. Furthermore, changes in cell cycle, mitochondrial transmembrane potential, calcium homeostasis and levels of reactive oxygen species were measured. Shikonin-treated SMMC-7721 cells exhibited morphological changes and DNA damage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Previous studies have shown that several plant extracts and active compounds induce caspase‐3‐mediated apoptotic cell death in hepatocellular carcinoma (Tang et al., 2020; Thakur & Devaraj, 2020). The pro‐apoptotic effect of shikonin is caused by the disruption of intracellular Ca 2+ homeostasis and mitochondrial dysfunction, activation of caspase‐3, caspase‐8, and caspase‐9 activities and regulation of Bcl‐2 family protein (Wang et al., 2018). One of the main active constituents of Stellera chamaejasme Linn.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that several plant extracts and active compounds induce caspase‐3‐mediated apoptotic cell death in hepatocellular carcinoma (Tang et al., 2020; Thakur & Devaraj, 2020). The pro‐apoptotic effect of shikonin is caused by the disruption of intracellular Ca 2+ homeostasis and mitochondrial dysfunction, activation of caspase‐3, caspase‐8, and caspase‐9 activities and regulation of Bcl‐2 family protein (Wang et al., 2018). One of the main active constituents of Stellera chamaejasme Linn.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple mechanisms involved in the anticancer effects of shikonin, including ER stress, ROS generation, glutathione (GSH) depletion, mitochondrial membrane potential disruption, p53, superoxide dismutase (SOD) and Bax up-regulation, PARP cleavage, catalase and Bcl-2 down-regulation [591,[612][613][614]. The pro-apoptotic effect of shikonin is also caused by the disruption of intracellular Ca 2+ homeostasis and mitochondrial dysfunction, which involves enhanced Ca 2+ and potassium (K + ) efflux, caspase-3, -8 and -9 activation, and Bcl-2 family protein modulation [615,616]. ERK pathway also plays a role in shikonin-induced anti-cancer effects.…”
Section: Shikoninmentioning
confidence: 99%
“…Changes in calcium ion levels in cell organelles are related to mitochondrial dysfunction and can cause apoptosis. For instance, intracellular calcium ion upregulation in human hepatoma cells is usually associated with oxidative stress and mitochondrial dysfunction, leading to antiproliferation and cell death [ 17 ]. The calcium levels in both the cytosol and mitochondrial matrix are involved in the progression of cancers including HCC [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%